2017
DOI: 10.1037/amp0000103
|View full text |Cite
|
Sign up to set email alerts
|

Advancing social connection as a public health priority in the United States.

Abstract: A robust body of scientific evidence indicates that being embedded in high-quality close relationships and feeling socially connected to the people in your life is associated with decreased risk for all-cause mortality as well as a range of disease morbidities. Despite mounting evidence that the magnitude of these associations is comparable to many leading health determinants (that receive significant public health resources), government agencies, healthcare providers and associations, and public/private healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
536
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 657 publications
(557 citation statements)
references
References 70 publications
(96 reference statements)
12
536
0
9
Order By: Relevance
“…In contrast, social isolation refers to a complete or near‐complete lack of contact with society, and it relates to a quantifiable number of relationships (actual isolation). Lastly, social connectedness refers to a multifactorial construct that represents the structural (eg, network size, marital status), functional (eg, perceived social support), and quality (eg, positive or negative) aspects of social relationships . On a continuum of low to high, isolation, loneliness, and relationship strain would be examples of low social connectedness …”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, social isolation refers to a complete or near‐complete lack of contact with society, and it relates to a quantifiable number of relationships (actual isolation). Lastly, social connectedness refers to a multifactorial construct that represents the structural (eg, network size, marital status), functional (eg, perceived social support), and quality (eg, positive or negative) aspects of social relationships . On a continuum of low to high, isolation, loneliness, and relationship strain would be examples of low social connectedness …”
Section: Epidemiologymentioning
confidence: 99%
“…Loneliness has received widespread national and international attention in the public press and in the medical literature. The relationship between loneliness health outcomes, particularly mortality, is as great as many traditional medical risk factors . For example, a recent meta‐analysis demonstrated that loneliness has a greater impact on health than obesity, physical inactivity, and air pollution .…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Involvement in a satisfying romantic relationship is a protective factor for many health conditions (Holt-Lunstad, Robles, & Sbarra, 2017;Holt-Lunstad, Smith, & Layton, 2010), in part because romantic partners have the ability to apply social influence, or interpersonal regulation, to improve each other's health behaviours (see meta-analytic review by Craddock, vanDellen, Novak, & Ranby, 2015). Importantly, however, people have their own reasons for employing interpersonal regulation.…”
mentioning
confidence: 99%
“…He theorized that the higher suicide rates among Protestants was related to lower social integration in their faith communities. This study's focus on sense of community and sense of belonging is further grounded in the substantial evidence linking social support to physical (Holt-Lunstad et al 2017) and psychological…”
mentioning
confidence: 99%